MEDIA PEMBELAJARAN BERBASIS ETNOMATEMATIKA : SYSTEMATIC LITERATURE REVIEW - Nugraha Wirawan Nugraha; Novaliyosi Novaliyosi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to evaluate the effect of the application of ethnomathematics-assisted learning media, which is studied based on the type of learning media. This study used the systematic literature review (SLR) method. Articles were searched on the Google Scholar, Sinta, Semantic Scholar, Education Resources Information Center (ERIC), and Directory Open Access Journal (DOAJ) databases from 2017 to 2023. Based on the established inclusion criteria, 25 articles were obtained, which were used as primary studies. Each article was recorded and then classified based on title, school year, education level, and type of media. The results showed that the integration of ethnomathematics-based learning media in mathematics learning had a positive effect on students' mathematics learning. The application of ethnomathematics is more often applied in the stages of junior high school education units. So that learning media is very suitable to be applied based on ethnomathematics to achieve goals, improve students' abilities, and introduce them to the culture that is around them and in Indonesia